Забезпечення мотивації майбутніх лікарів до ефективної професійно-орієнтованої комунікації засобами педагогічної взаємодії - Трегуб, Світлана Євгенівна (Science Review, 2018)
Професійна підготовка майбутнього лікаря – тривалий процес формування його не лише як фахівця, а і як особистості з особистісною спрямованістю на особистісне й професійне самовдосконалення впродовж усього життя. В умовах ринкової економіки, коли надання медичних послуг набуває професійної конкуренції та висуваються нові вимоги до особистості лікаря, зростає потреба в активізації його мовленнєвої культури. The article is devoted to the motivational filling analysis of future physicians’ professional culture of communication formation (PCC). The expediency of positive motivation’s development for getting professional knowledge, skills and abilities to carry out professional activity has been substantiated. The groups of motives that simultaneously influence on the educational process efficiency and the professional training of a modern physician have been identified. It was established that the future doctors’ professional culture of communication is as both an organic component and the index of professional and general culture, an important factor of its motivation, which expresses and determines the manner in which the person performs his professional tasks, characterizes social orientation on professional issues. It is noted, that the essence of future doctors’ professional culture of communication is not only the ability to communicate, but also a special attitude to health, which is the highest value.
Keywords: professional communicative culture (PCC); motivation; future physician; formation